Subjectivity Žižek’s Perspective in the Short Story Ash-Shabiyyu al-A‘raj by Taufiq Yusuf Awwad : Dhātiyyah fī Manẓūr Žižek fī al-Qiṣṣah al-Qaṣīrah Ash-Shabiyy al-A‘raj li Taufīq Yūsuf ‘Awwād - Afifah, Nur; Muhammad Reko (An-Nahdah Al-'Arabiyah, 2026)
This article aims to examine Žižek’s concept of subjectivity through a radical character in the short story Ash-Shabiyyu al-A’raj. This study employs a descriptive qualitative design with a textual approach, using the observation method with note-taking techniques, and is grounded in Slavoj Žižek’s theoretical framework. The novelty of this research lies in both the choice of the material object and the precision of applying Žižekian analysis to the short story. The findings reveal that the existence of radical actions carried out by the character Khalil is shaped by a period of confinement that forms a radical attitude as a response to internal attachment. Khalil undergoes the stages of the imaginary, the symbolic, and the real, which ultimately construct him as a radical subject. Thus, Slavoj Žižek’s theory is employed in this study to analyze the entity of the radical subject in the short story Ash-Shabiyyu al-A’raj. This research contributes to a more comprehensive understanding of Žižekian studies, particularly regarding the radical subject in Ash-Shabiyyu al-A’raj   يهدف هذا المقال إلى دراسة مفهوم الذاتية عند سلافوي جيجك من خلال شخصية راديكالية في القصة القصيرة الشاب الأعرج. وتعتمد هذه الدراسة المنهج الوصفي النوعي ذا المقاربة النصية، باستخدام أسلوب الملاحظة وتقنية تدوين الملاحظات، مستندةً إلى الإطار النظري لسلافوي جيجك. وتكمن جدة هذا البحث في اختيار موضوعه وفي دقة توظيف التحليل الجيجكي على النص القصصي المدروس. وتكشف النتائج أن وجود الأفعال الراديكالية التي يقوم بها بطل القصة، خليل، يتشكل من خلال فترة من العزلة والاحتجاز، أسهمت في تكوين موقف راديكالي بوصفه استجابة لتعلّق داخلي. ويمرّ خليل بمراحل المتخيَّل والرمزي والواقعي، التي تنتهي بتشكّله ذاتًا راديكالية. وبناءً على ذلك، تُوظَّف نظرية سلافوي جيجك في هذه الدراسة لتحليل كينونة الذات الراديكالية في القصة القصيرة الشاب الأعرج. وتسهم هذه الدراسة في إثراء الفهم الشامل للدراسات الجيجكية، ولا سيما فيما يتصل بمفهوم الذات الراديكالية في الشاب الأعرج.   Artikel ini bertujuan untuk mengkaji subjektifitas Žižek, melalui tokoh radikal di dalam cerpen Ash-Shabiyyu al-A’raj. Penelitian ini bersifat deskriptif kualitatif, pendekatan tekstual, metode simak teknik catat, berdasarkan teori Slavoj Žižek. Penelitian ini memiliki kebaruan dari segi objek material dan ketepatan analisis pemikiran Žižekian di dalam cerpen. Hasil penelitian menunjukkan, eksistensi tindakan radikal yang dilakukan oleh tokoh Khalil, disebabkan oleh masa belenggu yang membentuk sikap radikal, sebagai respon keterikatan di dalam diri. Tokoh Khalil mengalami masa the imaginary, the symbolic dan the real hingga menjadi subjek radikal. Dengan begitu, teori Slavoj Žižek digunakan dalam penelitian ini, untuk menganalisis entitas subjek radikal dalam cerpen Ash-Shabiyyu al-A’raj. Penelitian ini dapat memberikan kontribusi pada pemahaman yang lebih komprehensif terhadap kajian Žižek, khususnya pada subjek radikal dalam cerpen Ash-Shabiyyu al-A’raj.